Breakthrough Invasive Mold Infections in the Hematology Patient: Current Concepts and Future Directions. (31st May 2018) - Lionakis, Michail S; Lewis, Russell E; Kontoyiannis, Dimitrios P
Abstract : Despite the effectiveness of mold-active prophylaxis, breakthrough invasive mold infections (bIMIs) are encountered in high risk hematology patients. This viewpoint outlines different clinical scenarios and presents the diagnostic and treatment challenges of bIMIs in that patient population. Abstract: Although the widespread use of mold-active agents (especially the new generation of triazoles) has resulted in reductions of documented invasive mold infections (IMIs) in patients with hematological malignancies and allogeneic hematopoietic stem cell transplantation (HSCT), a subset of such patients still develop breakthrough IMIs (bIMIs). There are no data from prospective randomized clinical trials to guide therapeutic decisions in the different scenarios of bIMIs. In this viewpoint, we present the current status of our understanding of the clinical, diagnostic, and treatment challenges of bIMIs in high-risk adult patients with hematological cancer and/or HSCT receiving mold-active antifungals and outline common clinical scenarios. As a rule, managing bIMIs demands an individualized treatment plan that takes into account the host, including comorbidities, certainty of diagnosis and site of bIMIs, local epidemiology, considerations for fungal resistance, and antifungal pharmacological properties. Finally, we highlight areas that require future investigation in this complex area of clinical mycology.